Mental health of children and adolescents related to virtual education during the COVID-19 pandemic in Peru and measured by PSC-17 - Tirado Hurtado, Benilde (2025)
Objective: To assess the mental health of children and adolescents in connection with virtual education during the COVID-19 pandemic in Peru, using the PSC-17 scale. Materials and methods: Schoolchildren completed the Peruvian version of the PSC-17 through telephone calls or video calls between November 2021 and January 2022. The Chi-square test was used to evaluate the difference in the distribution of psychosocial problems between groups, and binary logistic regression to explore the possibly associated risk factors. Statistical analysis was performed through SPSS 22.0. Results: A total of 561 valid questionnaires were collected from 13 public and private schools. 52,6% of the proband schoolchildren presented diverse levels of stress, sadness, or irritability; and 34,8% expressed that the most demanding factor was the learning modality. 28,5% were at risk of presenting mental health problems (54,9% of them, internalizing problems, 25% attentional problems, and 2,9% externalizing problems); male probands showed a higher risk (p=0,016). Schoolchildren from public institutions presented a lower risk of experiencing mental health problems (p=0,039). Conclusion: Approximately one-third of schoolchildren were at risk of suffering from a mental health problem; among them, those from public institutions were at a lower risk. Students who felt stressed, sad, or irritated in virtual classes were more likely to experience mental health problems.